Comparison of 1D a 2D ITP‐MS performance parameters and application possibilities: Ultratrace determination of B vitamins in human urine. Issue 9 (12th October 2021) - Piestansky, Juraj; Cizmarova, Ivana; Matuskova, Michaela; Mikus, Peter
Abstract: The possibility to investigate analytes at ultra‐low concentration levels still remains a hot topic in bioanalysis. In this area, various preconcentration techniques are an integral part of analytical procedures. When applying electromigration separation techniques, an isotachophoresis has been advantageously employed many times for this purpose. To solve current biomedical tasks effectively, an advanced two‐dimensional isotachophoretic instrument (in a hydrodynamically closed separation system with an enhanced sample load capacity) hyphenated with mass spectrometry (ITP‐ITP‐MS) has been proposed by Foret and coworkers. As a continuation, this work represents the first study dealing with a full validation of an ITP‐ITP‐MS method. In order to see the benefits of an online ITP sample pretreatment (preconcentration and clean‐up) on the performance parameters, the developed 2D ITP‐MS method was compared with a corresponding 1D ITP‐MS method. Application potentialities of the compared methods were demonstrated via a determination of two B vitamins, namely thiamine and pyridoxine, in human urine samples. The developed 2D ITP‐MS method showed its enhanced effectivity and usefulness for a routine biomedical use (here, a reliable screening of trace B vitamins in human urine without an offline sample preparation).